Two new species of Trichoderma from (Hypocreaceae, Hypocreales) Jilin Province, China - Wang, Yu; Bau, Tolgor (Phytotaxa, 2026)
Based on morphological and molecular phylogenetic analyses, two new species of Trichoderma from China are described: Trichoderma jilinense and T. palmatum. Phylogenetic analyses based on a concatenated multi-gene (tef1-α and rpb2) dataset demonstrated that each new taxon formed an independent lineage with unique sequences, fulfilling the criteria for new Trichoderma species. Specifically, T. jilinense belongs to the Polysporum clade, and T. palmatum belongs to the Psychrophila clade. Morphologically, T. jilinense is diagnosed by relatively small part-ascospores and fresh beige to buff stromata that turn chestnut brown in 5% KOH, and relatively small part-ascospores. T. palmatum is distinguished by a fertile part that is palmate to irregular and typically laterally flattened.